Kitabü’z-zeyl ve et-tekmile : li kitabeyi’l-mevsûl ve es-sıla - 880-01 Ebû Abdullah Muhammed b. Muhammed b. Abdülmelik Ensârî el-Evsî el-Marâkeşî, 1237-1303. (Beyrut)
1. cilt (1. kısım 416 sayfa ; 2. kısım 416 sayfa)